Isolation and characterization of bacterial community from lake water for manganese removal: article - Jun, Noraprilenna; Subari, Fuzieah (2020)
Water scarcity was the result of imbalance natural phenomena across the world and attributed by the irresponsible act of human as well. A lot of cases reported worldwide on the contamination of heavy metal including manganese in water reservoir. Few methods applicable for manganese removal however biological method appear to be more promising than others. Biotic removal of soluble manganese (Mn2+) to insoluble manganese (manganese oxide) by the microorganism known as manganese oxidizing bacteria (MOB). The MOB is phylogenetically diverse and can be isolated from various sources like lake, ocean and many other places. Hence, this study will be focusing on isolation and characterization of pure culture originated from surface lake water. The pure isolation technique will be conducted to isolate the community to its single colony. After being isolated, Gram Staining Test will be used to characterize the isolated bacteria based on its cell wall constituents and will be observed by using microscope. The manganese tolerance test conducted to test the ability of the bacteria to grow in the presence of manganese at various concentration. The number of colonies formed plotted into a graph versus manganese concentration after 24 hours incubation period. Bacterial growth was monitored for 24 hrs and the result were plotted accordingly. This study was successfully isolated 7 bacteria from the surface lake water. All of them were classified gram positive bacteria and were tolerance to the manganese at 100 mg/L.